Molecular phylogenetic relationships within the subtribe Disinae (Orchidaceae) and their taxonomic, phytogeographic and evolutionary implications - Bytebier, Benny (Benny Leopold Germaine) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2007.